Reconstruction of Mining Policies on Justice in Lampung Province - Pane Erina; Adam Muhammad Yanis (Bestuur, 2020)
The purpose of research is to examine the mining potentials and policies that have been implemented in Lampung Province and to reformulate mining policies in Lampung Province, which on the one hand can improve the regional economy, on the other hand while maintaining environmental sustainability. Mining resources are a source of prosperity for the region, but it requires commitment from local governments, public institutions, the private sector and the community to conduct sustainable mining management. Sustainable management is able to meet the needs of the present, in the future and improve the health, prosperity of the environment and surrounding communities. Policies that can be carried out starting from licensing, monitoring post-mining land management, managing mine waste and compiling regulations that can support the realization of green mining and environmental conservation activities. The results of this study indicate that mining management in Lampung Province provides economic value to increase local revenue. However, it must be supported by environment-based policies, because mining activities have the possibility of an environment that becomes uncontrollably damaged. Efforts that can be done by local governments are by paying attention to licensing for managers, providing guidance, supervision, so that mining activities can be controlled and not damage the environment